IMPROVEMENT OF THE CASTINGS SURFACE QUALITY AS A RESULT OF APPLICATION OF SPHERICAL CHROMITE SPHERICHROME - A. A. Korobov (Литьë и металлургия)
Comparison of chrome sand of Republic of South Africa abd chromite of new generation Spherichrone (producer – the American company Oregon Resources corporation) for priduction of castings with surface of high quality is given.